PELATIHAN PENYUSUNAN ANGGARAN KAS BAGI HOME INDUSTRI MAKANAN DAN MINUMAN DI KOTA PALEMBANG - Gozali, Efva; Sari, Rela; Hamzah, Ruth Samantha; Nurullah, Asfeni (Jurnal Abdimas Musi Charitas, 2022)
This community service activity aims to determine the importance of budgeting, types and functions of cash, the purpose of preparing a cash budget, sources and uses of cash, factors that influence the preparation of a cash budget, the application of budgeting and cash budgeting methods to the Home Industry of Food and Beverage in Palembang City, of South Sumatra. The method used is lectures and discussions accompanied by the provision of simulations and mentoring for four months (August – November 2022). The visit was in the form of providing training materials which were given three times at different times. The results of this activity indicate that after being given training the Home Industry of food and beverage with knowledge of cash is accompanied by how to prepare and implement it.